2019
DOI: 10.3389/fpsyg.2019.00372
|View full text |Cite
|
Sign up to set email alerts
|

Self-Interest Induces Counter- Empathy at the Late Stage of Empathic Responses to Others’ Economic Payoffs

Abstract: Previous studies have found that individuals exhibit empathic responses when others are treated unfairly. However, there remains a lack of clarity over the extent to which self-interest regulates these empathic responses, and in identifying which component of empathy is more likely to be affected. To investigate these issues, an experiment was designed based on a money distribution task with two conditions [observation condition (OC) vs. participation condition (PC)], and carried out using scalp-recorded event… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 76 publications
(92 reference statements)
2
13
0
Order By: Relevance
“…As previously described, empathy relies on affective and cognitive components, as well as regulatory processes to maintain equilibrium between these components (e.g., Decety & Jackson, 2004). A speculative hypothesis is that the cognitive load could interfere with the cognitive component of empathy, possibly by affecting the mentalizing brain network, as suggested by previous studies (e.g., Gu & Han, 2007; Jie et al., 2019b; Morelli & Lieberman, 2013; Rameson et al., 2012; Spunt & Lieberman, 2013). This would then create an imbalance between the affective and cognitive components of empathy and force individuals to rely mostly on the affective component to generate empathic judgments.…”
Section: Studymentioning
confidence: 94%
“…As previously described, empathy relies on affective and cognitive components, as well as regulatory processes to maintain equilibrium between these components (e.g., Decety & Jackson, 2004). A speculative hypothesis is that the cognitive load could interfere with the cognitive component of empathy, possibly by affecting the mentalizing brain network, as suggested by previous studies (e.g., Gu & Han, 2007; Jie et al., 2019b; Morelli & Lieberman, 2013; Rameson et al., 2012; Spunt & Lieberman, 2013). This would then create an imbalance between the affective and cognitive components of empathy and force individuals to rely mostly on the affective component to generate empathic judgments.…”
Section: Studymentioning
confidence: 94%
“…The authors of that study argued that counter-empathy induced by unfair distribution was not a complete disregard for others’ interests but an emotional reaction accounting for others’ interests while focusing on one’s own interests. Their study showed that the relationship between counter-empathy and empathy may be a transformation relationship and not the opposite ( Jie et al. , 2019b ).…”
Section: Introductionmentioning
confidence: 99%
“…Second, counter-empathy may involve more complex psychological mechanisms than those of empathy. According to previous ERP studies, one reason for this is that counter-empathy induced by some contexts occurs at the late stages of empathic responses, exhibiting a transformation from empathy to counter-empathy ( Jie et al. , 2019b ; Fan et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Empathy gives us important information about other people and the environment, making it more possible to handle potential threat and promote prosocial behavior (Frith and Frith, 2006 ; Decety, 2010 ; Graaff et al, 2018 ). Several studies revealed that empathy is influenced by contextual factors, such as fairness (Singer et al, 2006 ), social distance (Meyer et al, 2012 ; Wang et al, 2016 ), competition (Yamada et al, 2011 ; Luo et al, 2018a ), state anxiety (Luo et al, 2018b ), self-interest (Jie et al, 2019a , b ), as well as social exclusion.…”
Section: Introductionmentioning
confidence: 99%